Are savings groups a livelihoods game changer for young people in Africa?. Issue 1 (2nd January 2018) - Flynn, Justin; Sumberg, James
ABSTRACT: The triad of entrepreneurship, self-employment, and financial inclusion underpins policy and development interventions meant to address the youth employment challenge in Africa. Youth savings groups are being widely promoted as a first step toward financial inclusion and economic empowerment. This article reports on the links between income-generating activities of 57 members of youth savings groups in Tanzania, Uganda, Zambia, and Ghana, and their membership in savings groups. It concludes that while savings groups can help to facilitate operational expenses and cash flow – and thus support members' micro-enterprises – in opportunity starved contexts their transformational potential is probably being oversold.